SIGNIFIKANSI INOVASI TEKNOLOGI DALAM KONTEKS EKSPANSI DAN TRANSFORMASI EKONOMI PASCA-PANDEMI - Ferdinand Tharorogo Wau; Mario Andrias Kiton (Journal Publicuho, 2024)
This research significance of technological innovation in the context of post-pandemic economic expansion and transformation is conducted. The research methodology involves a literature study and quantitative. The literature study focuses on the theory of technological innovation and empirical findings related to its impact on post-pandemic economic expansion and transformation. The results of the validity test indicate that the measurement instruments for technological innovation variables and economic expansion and transformation are statistically valid. Reliability tests using Cronbach's Alpha show an acceptable level of reliability for both variables. Simple regression analysis indicates a positive relationship between technological innovation and economic expansion and transformation of MSMEs. Hypothesis testing with the t-test confirms the significance of this relationship. Descriptive hypothesis testing indicates that technological innovation and economic expansion and transformation of MSMEs operate effectively, with agreement and strong agreement percentages reaching 94% for both variables. Normality testing shows that the residual values are normally distributed. This research provides a significant contribution to understanding the role of technological innovation in supporting the post-pandemic economic expansion and transformation of MSMEs. The practical implications of this research can assist entrepreneurs and policymakers in enhancing the implementation of technological innovation to support sustainable economic growth.